2021
DOI: 10.1017/s1431927621013878
|View full text |Cite
|
Sign up to set email alerts
|

Gray-Level Co-occurrence Matrix Analysis for the Detection of Discrete, Ethanol-Induced, Structural Changes in Cell Nuclei: An Artificial Intelligence Approach

Abstract: Gray-level co-occurrence matrix (GLCM) analysis is a contemporary and innovative computational method for the assessment of textural patterns, applicable in almost any area of microscopy. The aim of our research was to perform the GLCM analysis of cell nuclei in Saccharomyces cerevisiae yeast cells after the induction of sublethal cell damage with ethyl alcohol, and to evaluate the performance of various machine learning (ML) models regarding their ability to separate damaged from intact cells. For each cell n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“… 25 , 26 GLCM analysis is a contemporary and innovative computational method to assess the textural patterns applicable to most areas of microscopy. 27 To the best of our knowledge, this is the first study to create a relatively sensitive GLCM-based ML model for evaluating DMI. Based on the obtained GLCM data, we applied five ML approaches.…”
Section: Discussionmentioning
confidence: 96%
“… 25 , 26 GLCM analysis is a contemporary and innovative computational method to assess the textural patterns applicable to most areas of microscopy. 27 To the best of our knowledge, this is the first study to create a relatively sensitive GLCM-based ML model for evaluating DMI. Based on the obtained GLCM data, we applied five ML approaches.…”
Section: Discussionmentioning
confidence: 96%
“…This GLCM feature indicates textural homogeneity and is often used to quantify smoothness in the distribution of resolution units in grayscale images. Previous research articles in digital micrographs have shown the potential value of inverse difference moment in detecting structural alterations that are not visible to a professional pathologist ( 35 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the future, probably the most important application of both GLCM and DWT analyses will be to provide inputs for various artificial intelligence-based methods for image analysis in radiology. This application would include training and testing different machine learning models, some of which have already been suggested as suitable for GLCM data ( 44 ). The examples would be conventional decision tree algorithms such as CHAID (Chi-square Automatic Interaction Detector) or CART (classification and regression tree) or some more modern approaches such as random forests.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous articles, we applied similar GLCM approaches to analyze alterations to the renal vascular architecture 22 , highlighting its potential application in the characterization of whole organ scaffolds 23 that can be generated for bioarti cial kidney development 24 . Using this technique, We also examined cell nuclei after the damage induced by exposure to a sublethal toxic dose of ethanol 12 . On an experimental model of saccharomyces cerevisiae, we calculated angular second moment, inverse difference moment, textural contrast, GLCM correlation, and variance and demonstrated that these features signi cantly change after alcohol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The second technique is based on the discrete wavelet transform (DWT), a mathematical approach to the texture frequently applied for two-dimensional signal analysis as an addition to GLCM. Previous research has shown that both methods are potentially valuable tools in pathology for differentiating damaged and intact cells 11,12 . Also, both methods can be used to train and develop arti cial intelligence (AI) machine learning models, such as those based on decision trees, logistic regression, or arti cial neural networks.…”
Section: Introductionmentioning
confidence: 99%